2019
DOI: 10.1371/journal.pone.0215604
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic protective effects of a statin and an angiotensin receptor blocker for initiation and progression of atherosclerosis

Abstract: Aim Although the atheroprotective effects of statins and angiotensin II receptor blockers (ARBs) are well-established, little is known about their additive effects, especially during the early period of atherosclerosis. The aim of this study was to investigate whether combination of a statin and an ARB exerts synergistic anti-atherosclerotic effects, and to elucidate the mechanisms of combined effects. Methods Atherosclerotic plaques were developed in arteries of 23 rab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…The finding that pro-efferocytic therapies amplify the pleiotropic benefits of statins in mice is therefore interesting, particularly given our translational observation that statin usage is associated with lower vascular CD47 expression in humans. It is also important to note that this observed benefit occurs independent of classical risk factors like hypertension, glucose, and lipid levels, which is consistent with prior reports studying these agents in vascular models 11 , 13 , 33 35 . Because pro-phagocytic therapies reduce risk irrespective of traditional risk pathways (which can already be addressed with currently-available medicines), we hypothesize that reactivating intraplaque efferocytosis is an auspicious target for the residual inflammatory risk in atherosclerosis.…”
Section: Discussionsupporting
confidence: 90%
“…The finding that pro-efferocytic therapies amplify the pleiotropic benefits of statins in mice is therefore interesting, particularly given our translational observation that statin usage is associated with lower vascular CD47 expression in humans. It is also important to note that this observed benefit occurs independent of classical risk factors like hypertension, glucose, and lipid levels, which is consistent with prior reports studying these agents in vascular models 11 , 13 , 33 35 . Because pro-phagocytic therapies reduce risk irrespective of traditional risk pathways (which can already be addressed with currently-available medicines), we hypothesize that reactivating intraplaque efferocytosis is an auspicious target for the residual inflammatory risk in atherosclerosis.…”
Section: Discussionsupporting
confidence: 90%
“…These investigators found that Enalapril up-regulated the expression of the anti-inflammatory transcription factor peroxisome proliferator-activated receptors (PPAR)-gamma, adding mechanistic insight to this study. In one interesting report, a combination strategy was performed in which a statin was administered to hypercholesterolemic rabbits simultaneously with an AT1R blocker [ 62 ]. Plaque burden was inhibited more in the combination group compared with the statin alone group, again pointing to Ang II signaling as a pro-atherogenic event.…”
Section: Direct Causative Relationships Between Angiotensin II Andmentioning
confidence: 99%
“…In one randomized clinical trial, elderly human subjects treated with the angiotensin receptor blocker Valsartan demonstrated improved age-related vascular compliance [ 66 ]. In one longitudinal study, carotid artery stiffness was correlated with advancing age [ 62 ], but addition of anti-hypertensive therapy was significantly correlated with improved artery distensibility, linking age, artery stiffness, and hypertension.…”
Section: Angiotensin II Atherosclerosis and Vascular Agingmentioning
confidence: 99%
“…Other variables in groups 3 and 4, compared to those in the positive control group, were also substantially reduced, but failed to show statistically significant differences. Since there have been reports that statins exert prohibitory effects on atherosclerotic plaque formation by reducing macrophage content [ 19 , 24 ], the difference in the window period during which the rabbit carotid arteries were harvested between this study (1 week) and previous literature (2 or more weeks) was possibly the reason why our immunohistochemical results failed to show significance.…”
Section: Discussionmentioning
confidence: 67%